1995
DOI: 10.1055/s-0038-1642721
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Adhesion to Collagen

Abstract: Haemostasis-that is the arrest of bleeding-is achieved by the formation of an occluding haemostatic plug (1). As a first step of the haemostatic plug formation, platelets adhere to the perivascular connective tissue which has become exposed due to a breach in the vessel wall. This platelet adhesion is followed by spreading and activation, which results in secretion from platelet organelles and platelet aggregate formation. Platelet adhesion is crucial for thrombosis as well, particularly in arteries. In this c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 11 publications
2
39
0
1
Order By: Relevance
“…Likewise, the potency of peptide 6 is consistent with the evidence presented here that this peptide contains an ␣ 2 ␤ 1 recognition sequence. Our data lend support to the view (33, 34) that collagen-platelet interaction is a two-step process involving an initial recognition of adhesive sequences, such as those recognized by ␣ 2 ␤ 1 , as a primary interaction that may be especially important to retain platelets under flow conditions (7,35). Subsequent engagement with a second receptor induces signaling leading to platelet activation (aggregation).…”
Section: Discussionsupporting
confidence: 69%
“…Likewise, the potency of peptide 6 is consistent with the evidence presented here that this peptide contains an ␣ 2 ␤ 1 recognition sequence. Our data lend support to the view (33, 34) that collagen-platelet interaction is a two-step process involving an initial recognition of adhesive sequences, such as those recognized by ␣ 2 ␤ 1 , as a primary interaction that may be especially important to retain platelets under flow conditions (7,35). Subsequent engagement with a second receptor induces signaling leading to platelet activation (aggregation).…”
Section: Discussionsupporting
confidence: 69%
“…Collagen types I, II, III, and IV induce platelet adhesion (reviewed in Ref. 34). C.IV plays a role in cell migration and cell binding during tumor metastasis (35).…”
Section: Discussionmentioning
confidence: 99%
“…Some are not very potent inducers of adhesion/aggregation [22], The collagen in vascular basal lamina is type IV. Early reports [20,23] found that type IV collagen is unable to trigger adhesion/aggregation.…”
Section: Role Of Collagenmentioning
confidence: 99%